The Morphometrics of Mangrove Crabs (Scylla serrata) in the Essential Ecosystem Area (KEE) of Bagek Kembar Mangrove Forest, Sekotong, West Lombok - Diniah, Siti; Karnan, Karnan; Suyantri, Eni (Jurnal Biologi Tropis, 2024)
The intensive harvesting of Mangrove Crabs (Scylla serrata) has led to a significant decline in the population density of Scylla serrata in mangrove areas. Overfishing has resulted in a decrease in both the number and size of individual Mangrove Crabs and has altered the structure and composition of the population. This research aims to understand the morphometric characteristics of Scylla serrata, which will help sustain the population and protect mangrove areas as the native habitat for Scylla serrata and other organisms. Therefore, this study contributes to conservation and sustainable management efforts to ensure biodiversity. This type of research is descriptive-exploratory and aims to identify and analyze the size variations of Scylla serrata. The study was conducted at four points in the Essential Ecosystem Area (EEA) of Bagek Kembar Mangrove Forest, Sekotong, West Lombok, in both natural and rehabilitated zones. The results of this study found that the ratio of female to male Mangrove Crabs is 36:32, with females being more dominant in number. The morphometric characteristics of Mangrove Crabs in the Bagek Kembar Essential Ecosystem Area showed relatively uniform sizes across all sampling points, but some characteristics such as dactyl length, weight, and dactyl width showed significant differences, which may be influenced by the physiological condition of Scylla serrata and habitat conditions.